On the role of scales in elastomer friction; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Popov V. L. Valentin Leonidovich (2014, 2014)
Title screen